The Quaternary Structure of Amalgam, a Drosophila Neuronal Adhesion Protein, Explains Its Dual Adhesion Properties - Zeev-Ben-Mordehai, Tzviya (The Biophysical Society, 2009)
Amalgam (Ama) is a secreted neuronal adhesion protein that contains three tandem immunoglobulin domains. It has both homophilic and heterophilic cell adhesion properties, and is required for axon guidance and fasciculation during early stages of Drosophila development. Here, we report its biophysical characterization and use small-angle x-ray scattering to determine its low-resolution structure in solution. The biophysical studies revealed that Ama forms dimers in solution, and that its secondary and tertiary structures are typical for the immunoglobulin superfamily. Ab initio and rigid-body modeling by small-angle x-ray scattering revealed a distinct V-shaped dimer in which the two monomer chains are aligned parallel to each other, with the dimerization interface being formed by domain 1. These data provide a structural basis for the dual adhesion characteristics of Ama. Thus, the dimeric structure explains its homophilic adhesion properties. Its V shape suggests a mechanism for its interaction with its receptor, the single-pass transmembrane adhesion protein neurotactin, in which each “arm” of Ama binds to the extracellular domain of neurotactin, thus promoting its clustering on the outer face of the plasma membrane.